Encourage Student's Critical Thinking Skills Through Questioning on Simple Machine Materials - Padillah Chairani; Sardianto Markos Siahaan; Apit Fathurohman (Jurnal Pembelajaran Fisika, 2022)
This study aims to encourage students' critical thinking skills with teacher questions in the learning design defined by Bloom's Taxonomy. The research took data from the teacher's list of questions and students’ answers during the learning process which was carried out for three meetings. Learning activities are carried out for class VIII which consists of 33 junior high school students on simple machine material. Data collection used non-participatory observation and document content analysis to analyze the teacher's questions with Bloom's Taxonomy which became the criteria set for the level of questions. The results of the analysis showed that the distribution of high-level questions reached 54.05% with a total of 20 questions and 45.95% of low-level questions appeared with a total of 17 questions. Student activity in the learning process is observed and a checklist is carried out with the instrument showing the emergence of sub-critical thinking skills in student answers. Students experienced an increase in practicing critical thinking in their learning process. Overall, students critical thinking skills were observed at 73% in three meetings. Based on the results of this research, questioning in the class has been encouraged by ongoing learning that trains students' critical thinking skills.Keywords: Questioning, Critical thinking, Simple MachinesDOI: http://dx.doi.org/10.23960/jpf.v10.n2.202201